Graft‐versus‐host disease, a rare complication after orthotopic liver transplantation. Issue 1 (7th December 2017) - Ofosu, Andrew; Zabolotsky, Andrew; Rufail, Miguel; Spataro, Joseph; Civan, Jesse
Key Clinical Message: Acute graft‐versus‐host disease (GVHD) after orthotopic liver transplantation (OLT) is a rare but fatal complication that poses a major diagnostic and therapeutic challenge. Our case highlights the need for further studies to develop therapeutic modalities to improve outcomes in patients who develop GHVD following OLT. Abstract : Acute graft‐versus‐host disease (GVHD) after orthotopic liver transplantation (OLT) is a rare but fatal complication that poses a major diagnostic and therapeutic challenge. Our case highlights the need for further studies to develop therapeutic modalities to improve outcomes in patients who develop GHVD following OLT.